2018
DOI: 10.3390/catal8120668
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficiency of N-Doped TiO2 and N-Doped Bi2MoO6 Photo Catalysts for MB and Lignin Photodegradation

Abstract: In this study, we tested the efficiency of nitrogen-doped titanium dioxide (N-TiO2) and nitrogen-doped bismuth molybdate (N-Bi2MoO6) compounds as photocatalysts capable of degrading methylene blue and lignin molecules under irradiation with ultraviolet (UV) and visible light (VIS). Moreover, we compared TiO2 and Bi2MoO6 catalysts with N-TiO2 and N-Bi2MoO6 compounds using chemical coprecipitation. The catalysts were prepared starting from Ti(OCH2CH2CH3)4, Bi(NO3)3·5H2O, and (NH4)6Mo7O24 reagents. N-doping was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The dopednitrogen such as N in the O-Ti-N linkage mostly existed as nitrides species, attributed to the binding energy (BE) of 399.4 eV, and only small amounts were present as surface adsorbed ammonia, corresponding to the BE peak located at 396.0 eV. This result are in agreement with those reported in the XPS result of N-doped TiO2 (Boningari et al, 2018;Rangel et al, 2018;Yoshida et al, 2015). Zhang et al found a higher N1s binding energy as the N in the N-Ti-O due to higher electronegativity of O than N leads to the higher N electron density in the N-Ti-O structure than that of N in the N-Ti-N structure (Zhang et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…The dopednitrogen such as N in the O-Ti-N linkage mostly existed as nitrides species, attributed to the binding energy (BE) of 399.4 eV, and only small amounts were present as surface adsorbed ammonia, corresponding to the BE peak located at 396.0 eV. This result are in agreement with those reported in the XPS result of N-doped TiO2 (Boningari et al, 2018;Rangel et al, 2018;Yoshida et al, 2015). Zhang et al found a higher N1s binding energy as the N in the N-Ti-O due to higher electronegativity of O than N leads to the higher N electron density in the N-Ti-O structure than that of N in the N-Ti-N structure (Zhang et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…The value of valence band maximum (VBM) has shifted toward the lower energy (~1.1 eV) of BMO-CTAB (BMO, ~1.5 eV). It demonstrates that the process helps to reduce the separation of the valence band energy level from the Fermi level, which may reduce the concentration of electrons, and promote the generation of hydroxyl radicals (OH) in the photocatalytic process [40][41][42]. In order to further study the information of the crystal structure, infrared spectroscopy and Raman spectroscopy were performed, and the results are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Fibers are also susceptible to different types of degradation, such as ultraviolet (UV) and fire degradation due to lignin, as well as thermal degradation due to hemicellulose. 108 The degradation of green composites is also affected overall by the environmental conditions to which the material is exposed. Moisture, UV radiation, temperature, and microorganism activity can negatively impact the interfacial adhesion, causing micro-and macro-cracks in the material, accelerating the biodegradation of the composite.…”
Section: Biodegradability and Recyclabilitymentioning
confidence: 99%
“…Fibers are also susceptible to different types of degradation, such as ultraviolet (UV) and fire degradation due to lignin, as well as thermal degradation due to hemicellulose. 108…”
Section: Physical and Chemical Characteristics Of Renewable Recyclabl...mentioning
confidence: 99%